Oxidation of Styrene to Benzaldehyde Using Environmentally Friendly Calcium Sulfate Hemihydrate-Supported Titania Catalysts - Koesnarpadi, Soerja; Wirawan, Teguh; Nurhadi, Mukhamad; Wirhanuddin, Wirhanuddin; Prananto, Yuniar Ponco; Nazarudin, Nazarudin; Degirmenci, Volkan; Lai, Sin Yuan; Nur, Hadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This paper presents the synthesis and characterization of calcium sulfate hemihydrate (CSH)-supported titania (TiO2) catalysts and their application in the environmentally friendly oxidation of styrene to benzaldehyde using hydrogen peroxide (H2O2) as the oxidant. The study explores the catalyst's structure-activity relationship, emphasizing the importance of mesoporous materials for enhanced catalytic performance. The CSH-Titania catalysts were synthesized using fish bone-derived CSH as a support, which aligns with green chemistry principles. Characterization techniques such as Fourier Transform Infra Red (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Brunauer-Emmett-Teller (BET) surface area analysis confirmed the successful impregnation of titania and its catalytic efficiency. The catalysts exhibited high selectivity for benzaldehyde, achieving up to 49.45% conversion of styrene, with benzaldehyde as being the main product. The research highlights that the catalyst’s performance decreased after calcination due to a reduced surface area and pore volume, yet it maintained recyclability across three cycles with minimal lose in selectivity loss. Overall, this study introduces a cost-effective and sustainable approach to styrene oxidation, demonstrating the potential for industrial application in producing high-value chemicals with minimal environmental impact. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).